BIG DATA AND ARTIFICIAL INTELLIGENCE: SHAPING THE FUTURE - Nasriddinov Burhoniddin Zuhriddin o’g’li (World Scientific Research Journal, 2025)
In today's digital age, the terms "Big Data" and "Artificial Intelligence" (AI) are ubiquitous. They're driving revolutionary changes not just in technology, but in almost every aspect of our daily lives. This article explores the essence of Big Data and AI, their intricate relationship, and their immense potential for the future.What is Big Data?Big Data refers to incredibly large, diverse, and rapidly changing datasets that traditional database systems struggle to process. It's characterized by three primary features, often called the "three Vs":• Volume: Enormous quantities of data, often measured in terabytes, petabytes, or even exabytes.• Velocity: The speed at which data is generated and processed, often in real-time.• Variety: The diverse types of data, including unstructured (text, images, video), semi-structured (JSON, XML), and structured (tabular) data.